2014
DOI: 10.1128/aac.00125-14
|View full text |Cite|
|
Sign up to set email alerts
|

Population Structure of KPC-Producing Klebsiella pneumoniae Isolates from Midwestern U.S. Hospitals

Abstract: Genome sequencing of carbapenem-resistant Klebsiella pneumoniae isolates from regional U.S. hospitals was used to characterize strain diversity and the bla KPC genetic context. A phylogeny based on core single-nucleotide variants (SNVs) supports a division of sequence type 258 (ST258) into two distinct groups. The primary differences between the groups are in the capsular polysaccharide locus (cps) and their plasmid contents. A strict association between clade and KPC variant was found. The bla KPC gene was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 30 publications
(29 reference statements)
7
61
0
Order By: Relevance
“…Although most of the colistin-resistant strains were related clones, except for Col4 and Col22, our strains did not consist of identical strains (Table 1; see also Table S2 in the supplemental material). As in a previous study (25), this study also showed correlations between capsular type and ST. The predominant capsular type of colistin-resistant K. pneumoniae in Taiwan was K64, and the MLST results revealed that about half of the colistin-resistant isolates were ST11, similar to the results of a previous report in Spain (26).…”
supporting
confidence: 71%
“…Although most of the colistin-resistant strains were related clones, except for Col4 and Col22, our strains did not consist of identical strains (Table 1; see also Table S2 in the supplemental material). As in a previous study (25), this study also showed correlations between capsular type and ST. The predominant capsular type of colistin-resistant K. pneumoniae in Taiwan was K64, and the MLST results revealed that about half of the colistin-resistant isolates were ST11, similar to the results of a previous report in Spain (26).…”
supporting
confidence: 71%
“…Clinically, AMR phenotypes are monitored routinely in most hospital laboratories; however, our study indicates that it also will be crucial to perform active surveillance for key virulence genes and to determine clonal background. Genomic surveillance is being used increasingly to monitor KPC-producing K. pneumoniae, especially ST258, and the emergence of NDM-1 and colistin-resistant (XDR) isolates (27,28,(65)(66)(67). Crucially, our study shows that we can augment these surveillance efforts by using key virulence genes as strong predictors of invasive disease in humans, and by determining clonal background, so that we can identify and track XDR hypervirulent clones as they emerge.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent genomic analyses indicate that sequence type (ST) 258 is a recombinant strain that has undergone capsular exchange since its emergence as a cause of KPC outbreaks (28)(29)(30). However, little attention has been paid to other MDR clones, which also are common and can spread carbapenem resistance (31).…”
Section: Significancementioning
confidence: 99%
“…Strains originated from a collection of KPC-producing K. pneumoniae isolates obtained from a consortium of tertiary-care hospitals previously described (16,17). Colistin MICs were determined with a Sensititre system (17) and confirmed by Etest strips (bioMérieux). Genome sequencing was previously described (17) and consisted of Illumina HiSeq reads assembled with Newbler and annotated using the Comprehensive Microbial Resource annotation pipeline (18).…”
Section: Methodsmentioning
confidence: 99%
“…Strains originated from a collection of KPC-producing K. pneumoniae isolates obtained from a consortium of tertiary-care hospitals previously described (16,17). Colistin MICs were determined with a Sensititre system (17) and confirmed by Etest strips (bioMérieux).…”
Section: Methodsmentioning
confidence: 99%